The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5ob01032b
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic applications of hypophosphite derivatives in reduction

Abstract: The development of new tools for the reduction of organic functions to reach high chemo- and stereo-selectivity is an important research domain. Although, aluminum and boron hydrides are commonly used, they suffer from environmentally and safety issues. In particular, at industrial scale, the search for more specific and efficient reagents with a lower ecological impact remains one of the main objectives of organic chemists. This review captures highlights from literature concerning phosphonic and phosphinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 291 publications
0
13
0
Order By: Relevance
“…These features are optimal for application in radical chain dehalogenation and deoxygenation reactions, where hypophosphites have been used as a water-soluble, nontoxic, and inexpensive alternative to tin hydrides (Scheme ). It is important to note that phosphorus radicals are however less effective at XAT than tin and silicon radicals and often engage in competitive addition to olefins (hydrophosphination). , Indeed, mechanistic work carried out by Ingold on (EtO) 2 (O)­P• demonstrated that bromine abstraction with this species is 2 orders of magnitude slower than with Bu 3 Sn• . Further study on different phosphorus radicals demonstrated that their reactivity toward XAT decreases with the radical planarization, which translates into a lower spin density at the P-atom. , …”
Section: Applications Of Xat Reactivity In Synthetic Photocatalysismentioning
confidence: 99%
“…These features are optimal for application in radical chain dehalogenation and deoxygenation reactions, where hypophosphites have been used as a water-soluble, nontoxic, and inexpensive alternative to tin hydrides (Scheme ). It is important to note that phosphorus radicals are however less effective at XAT than tin and silicon radicals and often engage in competitive addition to olefins (hydrophosphination). , Indeed, mechanistic work carried out by Ingold on (EtO) 2 (O)­P• demonstrated that bromine abstraction with this species is 2 orders of magnitude slower than with Bu 3 Sn• . Further study on different phosphorus radicals demonstrated that their reactivity toward XAT decreases with the radical planarization, which translates into a lower spin density at the P-atom. , …”
Section: Applications Of Xat Reactivity In Synthetic Photocatalysismentioning
confidence: 99%
“…Nevertheless, the existing Lindlar-type reactions inevitably use high-pressure hydrogen as the hydrogen source, which poses a number of limitations to the reaction, such as potential explosion hazards, cumbersome operations for the use of high-pressure hydrogen, possible over-hydrogenation, and isomerization side reactions. In order to tackle these shortcomings, synthetic scientists developed the transfer hydrogenation reactions, [ 38 , 39 ] which use stable and easily handled reducing agents such as silanes [ 40 , 41 ], formic acid [ 42 ], alcohols [ 43 , 44 ], ammonia borane [ 45 , 46 ], DMF [ 47 ], hypophosphoric acid [ 48 , 49 ], and amines [ 50 ] as indirect hydrogen sources ( Figure 2 b), avoiding the use of flammable hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…[1,36,[45][46][47][48] Hydro-dehalogenation of aryl halides can be carried out in the presence of a suitable catalyst and hydrogen source. The hydrogen sources commonly used in the hydrodehalogenation reaction are metal hydrides, [3,49] sodium borohydrde, [3] hydrazine, [50,51] formic acid, [52] sodium formate, [53] various categories of hypophosphite derivatives, [54] borane dimethyl amine (Me 2 NH⋅BH 3 ), [55,56] tributyltinhydride (Bu 3 SnH), [57] hydrosilanes (HSiR 3 ), [58,59] and molecular hydrogen. [60] Alkali metal formates are one of the effective sources of hydrogen and decompose to molecular hydrogen and bicarbonate salt in presence of water and catalyst.…”
Section: Introductionmentioning
confidence: 99%